First-principles study of ferromagnetism in Pd-doped and Pd- Cu-codoped BN. Issue 1 (July 2016) - Wang, Q; Wang, S; Dai, J F; Li, W X
Abstract: In this paper, we aimed at probing the ferromagnetism properties of Pd and Pd-Cu- codoped supercell BN based on the first-principles methods. The formation energy, lattice constants, energy band structures, spin density of state, energy difference between ferromagnetism (FM) and autiferromagnetism (AFM) orderings were calculated. Formation energy calculations showed that Pd atom tended to replace B atom in the supercell. Pd-doped BN exhibited a half-metallic ferromagnetic. And the ferromagnetism arised form the strong hybridization between the Pd4d and N2p state. Pd-Cu-codoped BN also displayed a half-metallic ferromagnetic. The incorporation of Pd and Pd-Cu induced some impurity energy differences between FM and AFM orderings. It also showed that FM state was the ground state, and room temperature ferromagnetism may be expected. These results pointed out the possibility of fabricating BN based on dilute magnetic semiconductors (DMS) by doping with Pd and Pd-Cu.